2021
DOI: 10.3390/polym13020262
|View full text |Cite
|
Sign up to set email alerts
|

The Adverse Effects of TiO2 Photocatalycity on Paraloid B72 Hybrid Stone Relics Protective Coating Aging Behaviors under UV Irradiation

Abstract: The incorporation of photocatalytic nanomaterials into polymer coatings is used to protect stone relics from weathering. However, the photocatalytic nanomaterials might generate excess free radicals to degrade the polymer matrix. In this work, a certain amount of TiO2 nanoparticles were dispersed into Paraloid B72 and applied onto sandstone relics to explore the adverse effects of TiO2 nanoparticles on Paraloid B72 under ultraviolet (UV) irradiation. To fulfill this goal, the effects of TiO2 on pore formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Negligible variations were instead observed in PB72 samples without TiO 2 nanoparticles after 168 h of exposure. This behavior can be reasonably ascribed to the de-polymerization reactions in the polymer chain promoted by the photo-degradative action of TiO 2 nanoparticles, according to the mechanism proposed by Li W. et al [9]. In line with this interpretation is the overall decrease in intensity of the absorption in the FTIR spectra of Paraloid films treated with the nanodispersion after exposure.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Negligible variations were instead observed in PB72 samples without TiO 2 nanoparticles after 168 h of exposure. This behavior can be reasonably ascribed to the de-polymerization reactions in the polymer chain promoted by the photo-degradative action of TiO 2 nanoparticles, according to the mechanism proposed by Li W. et al [9]. In line with this interpretation is the overall decrease in intensity of the absorption in the FTIR spectra of Paraloid films treated with the nanodispersion after exposure.…”
Section: Discussionsupporting
confidence: 61%
“…Recent studies carried out on films of the acrylic polymer Paraloid B72 (a copolymer of methyl acrylate/ethyl methacrylate 30/70 % w/w), containing nanostructured TiO 2 have shown some degradation effects due to photo ageing [8,9]. Acrylic coatings have been used in the field of cultural heritage conservation since 1930 thanks to their ease of removal, transparency, absence of color, and ease of applicability in a thin coating [10].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with D, the UVA resistance of DT was lower. This may have been due to the photocatalytic activity of TiO 2 under UV light, which degraded DTMS under UVA irradiation [51], causing a decrease in its original hydrophobic property. Another explanation is that TiO 2 is photophilic [52] and hydrophilic under UV radiation, adsorbing invisible water films and causing a decrease in the contact angle [53].…”
Section: Uv Shielding Performancementioning
confidence: 99%
“…Many different kinds of inorganic nanometric reinforcing agents, such as TiO 2 and SiO 2 , were incorporated with organic polymers by scientists who sought better conservation material [15]. Nevertheless, recent results showed that the added TiO 2 nanoparticles can cause the degradation of the incorporated Paraloid B-72 after exposure to UV light for a certain period of time; other outcomes also indicate that the durability of these organicinorganic hybrid materials are not satisfying [16]. Conversely, the inorganic materials show high compatibility with the protected inorganic substrates; thus, leading to high durability.…”
Section: Introductionmentioning
confidence: 99%